EFFICIENCY OF ARTIFICIAL COLD PRODUCTION IN SEPARATION FREEZE-OUT PLANTS - Korotkiy I.A.; Korotkaya E.V.; Kurbanova M.G. (Техника и технология пищевых производств)
The article presents the results of research on energy efficiency of using various refrigerants in single-stage cold supplying systems of separation freeze-out plants. Separation freeze-out is used for low temperature concentration of liquid foods, water purification, separation and concentration of aqueous solutions. The volume of energy consumption in separation freeze-out is determined by the temperature of the object to be concentrated and that of the environment, as well as by thermodynamic properties of the refrigerant. Analytically, using known thermodynamic relations we have determined the energy consumption required for crystallization of 1kg of water from the solution when single-stage refrigerators using R-717, R-134a, R-22, R-404a, and R-410a as refrigerants are applied to remove heat of crystallization. The data have been obtained in the temperature range of boiling of the refrigerant from -5? C to-30? C and ambient temperatures from 15? C to 35? C. On the basis of thermodynamic analysis it has been found that a cold supplying system using R-22 as the refrigerant has better energy and operational efficiency for separation freeze-out plants. A coldsupplying system using ammonia has better energy efficiency compared to the ones using other refrigerants in a more restricted operating range, the refrigerant boiling point being above -20? C. In addition, the use of ammonia refrigerating systems for separation freeze-out is limited by constructive features. The use of R-134a refrigerant in the cold supplying system will lead to a significant increase in energy consumption for separation freeze-out compared to other cooling agents. R-410a can be a worthy replacement for R-22 after its withdrawal from use in the refrigeration industry for use in separation freeze-out plants.